The Model of Purchase Decision in The Online Stores Application Integration of Technology Acceptance Model, Personal Factors, Product Quality, and Price - Sharnuke Asrilsyak; Yuliarni Putri; Abdul Malik Sayuti; Chandra Budhi Septyandi; Wahyu Rafdinal (Jurnal Riset Bisnis dan Investasi, 2021)
This study aims to analyze the factors which influence an individual in making a purchase in online stores. It investigates the factors of technology acceptance (theory of acceptance model), personal (lifestyle and trust), product quality, and price in an online store. There are 180 who have bought products in the online stores. The data analysis technique used is the Structural Equation Model based on Partial Least Square. The results prove that from the technology acceptance explained by TAM indicates that only perceived usefulness significantly influential toward attitude. Then, it also denotes that attitude, product quality, price, lifestyle, and trust can influence purchase decisions in the online store applications by explaining the relation among technology acceptance models, personal factors (lifestyle and trust), product quality, and price.